2018
DOI: 10.3390/app8081398
|View full text |Cite
|
Sign up to set email alerts
|

Cartilage Differentiation of Bone Marrow-Derived Mesenchymal Stem Cells in Three-Dimensional Silica Nonwoven Fabrics

Abstract: In cartilage tissue engineering, three-dimensional (3D) scaffolds provide native extracellular matrix (ECM) environments that induce tissue ingrowth and ECM deposition for in vitro and in vivo tissue regeneration. In this report, we investigated 3D silica nonwoven fabrics (Cellbed®) as a scaffold for mesenchymal stem cells (MSCs) in cartilage tissue engineering applications. The unique, highly porous microstructure of 3D silica fabrics allows for immediate cell infiltration for tissue repair and orientation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 59 publications
1
8
0
Order By: Relevance
“…We may conclude that culture conditions are an essential factor for chondrogenic potential. This observation may be supported by other data which revealed that microenvironmental factors in a co-culture system may enhance the cooperation between different subpopulations of cells, and the interactions between them are important for their growth and differentiation [ 1 , 11 , 21 , 35 , 36 , 41 ].…”
Section: Discussionsupporting
confidence: 63%
“…We may conclude that culture conditions are an essential factor for chondrogenic potential. This observation may be supported by other data which revealed that microenvironmental factors in a co-culture system may enhance the cooperation between different subpopulations of cells, and the interactions between them are important for their growth and differentiation [ 1 , 11 , 21 , 35 , 36 , 41 ].…”
Section: Discussionsupporting
confidence: 63%
“…This trend is also suggested by the expression of osteocalcin (OCN) ( Figure 6 b). Moreover, MSC on SNF dominantly differentiated into chondrogenic cell, as compared with conventional spheroid and atelocollagen gel culture [ 61 ]. These results suggested that 3D SNFs are potential scaffolds for tissue engineered osteochondral construct, originated from highly porous and elastic SNF characters.…”
Section: Cell Scaffolds For Bone Tissue Regeneration Using Mscsmentioning
confidence: 99%
“…With continued catalyst development, Pourghasemi-Lati and colleagues (Pourghasemi-Lati et al, 2018) immobilized butane-1-sulfonic acid on magnetic Fe 3 O 4 @SiO 2 nanoparticles for the synthesis of 5-arylidine barbituric acids and pyrano [2,3-d] pyrimidine derivatives. In addition, silica-based biomaterials have been widely studied in bone and cartilage tissue engineering due to high mechanical stiffness, high biocompatibility, and special bioactivities including stimulating osteogenesis and angiogenesis by enhancing corresponding gene expressions (Li et al, 2000;Du et al, 2015;Ishikawa et al, 2018). For example, silica based inorganic/organic hybrids could promote collagen Type II, Sox9 and Aggrecan production from chondrocytes (Nelson et al, 2021) or have mechanically strong and elastic characteristics (Yu et al, 2021).…”
Section: Introductionmentioning
confidence: 99%